2021
DOI: 10.1073/pnas.2008814118
|View full text |Cite
|
Sign up to set email alerts
|

Measuring voluntary and policy-induced social distancing behavior during the COVID-19 pandemic

Abstract: Staying home and avoiding unnecessary contact is an important part of the effort to contain COVID-19 and limit deaths. Every state in the United States enacted policies to encourage distancing and some mandated staying home. Understanding how these policies interact with individuals’ voluntary responses to the COVID-19 epidemic is a critical initial step in understanding the role of these nonpharmaceutical interventions in transmission dynamics and assessing policy impacts. We use variation in policy responses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 44 publications
5
113
0
Order By: Relevance
“…We assumed a stable distribution of delays between infection and the time of confirmation or death, though this could have varied over the course of the outbreak 20 . Not all behavioral change is captured by concrete policies (e.g., voluntary behavior in response to the locally reported cases, which can be displaced by the mandate orders 21 ); however, our focus was on the possible impact of policies enacted by governments rather than actions taken by individuals in the absence of such policies.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed a stable distribution of delays between infection and the time of confirmation or death, though this could have varied over the course of the outbreak 20 . Not all behavioral change is captured by concrete policies (e.g., voluntary behavior in response to the locally reported cases, which can be displaced by the mandate orders 21 ); however, our focus was on the possible impact of policies enacted by governments rather than actions taken by individuals in the absence of such policies.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, Berry et al [47] found little evidence to support that shelter-in-place orders affected disease spread or fatalities. Comparisons of voluntary mitigative actions versus mandatory stay-at-home orders found that, in counties with existing voluntary behaviors, the mandates simply accelerated compliance [48]. However, not all sociodemographic groups have the social or economic capital available to partake in voluntary mitigative action and can thus suffer worse economic burdens from such imposed mitigation orders [49].…”
Section: Covid-19 Mitigation and Pre-emergent Recoverymentioning
confidence: 99%
“…In states with strict restriction policies, people spent much more time at home and made less movement during the pandemic, including traveling, recreation, grocery shopping, etc. ; and much less people moved between different cities and states [27][28][29]. The less strict policies may introduce more social factors into the analysis that we cannot determine easily at this point.…”
Section: Discussionmentioning
confidence: 98%